PEDAGOGICAL EFFECTIVENESS OF REAL-LIFE ORIENTED TASKS IN THE DEVELOPMENT OF FUNCTIONAL LITERACY IN PRIMARY GRADES - Turdiyeva Shahlo Sardor qizi (Bright Mind Publishing, 2026)
The article analyzes the pedagogical effectiveness of real-life oriented tasks in the formation and development of functional literacy in primary grade students. The study highlights the role of real-world situation-based tasks in the development of students' reading literacy, logical thinking, problem solving, practical calculation, and communicative competencies. Mechanisms for integrating real-life tasks into the lesson process, methodological recommendations and expected results are also justified. This approach is shown in scientific and practical terms as an important factor in increasing students' motivation for education, the formation of skills in applying knowledge in everyday life.
Keywords: Functional Literacy, Real-Life Oriented Tasks, Primary Education, Competency Approach, Problem Solving, Reading Literacy, Applied Mathematics, Integrative Education.